Books Completed or in Progress by Academy Members (Academy of Management Journal, 1963)
The article presents a list of books related to management. They include “Executive Decisions,” by Rossall J. Johnson, “Scientific Administration,” by Paul M. Dauten, and “Management Development: Prediction, Design, Installation and Measurement,” by Robert J. House.